Стратегия развития НКР на современном этапе в координатах внешнеэкономического пространства - Петросян, И.
The economic development strategy of Nagorno-Karabakh Republic in world economic system is a constituent of the whole economic development strategy of the country. Individual instruments and regulatory measures do not solve the problems of foreign-economic activities transformation on global basis, because NKR is not yet a legal entity and also the internal development processes should dominate and define the specific forms, directions and methods of integration into the international market in the initial phase of institutional changes. It is purposeful to develop the criteria and appraisals (measures) of economy’s functioning effectiveness on international market, creation of such factor conditions as quality and size of labor force, appropriate infrastructure, etc; conditions of demand on given production in internal market, companies’ functioning conditions, mechanisms of their creation, also competition conditions in internal market. Competitive advantages formation of NKR national economy is directly related to internal social-economic development. Համաշխարհային տնտեսական համակարգում ԼՂՀ տնտեսության զարգացուման ռազմավարությունը երկրի տնտեսական զարգացման ընդհանուր ռազմավարության μախկացուցիչ մասն է: Առանձին գործիքներն ու կարգավորող միջոցառումները չեն լուծում արտաքին տնտեսական գործունեության փոխակերպման խնդիրները համընդհանուր հիմքով, պայմանավորված է նրանով, որ ԼՂՀ-ն դեռ չի հանդիսանում իրավաμանական անձ միջազգային շուկայում: Նպատակահարմար է մշակել ԼՂՀ տնտեսության ՝ միջազգային շուկայում արդյունավետ գործնունեության չափանիշնեն ու գնահատականները, ստեղծել գործոնային պայմաններ ինչպիսիք են` աշխատուժի որակն ու արժեքը, համապատասխան ենթակառուցվածքը և այլն, սահմանել ներքին շուկայում տվյալ ապրանքատեսակի պահանջարկի պայմանները, կազմակերպությունների գործունեության պայմաններն ու դրանց ստեղծման մեխանիզմները, սահմանել ներքին շուկայի մրցակցության պայմանները: ԼՂՀ ազգային տնտեսության մրցակցության առավելությունների մշակումը ուղղակիորեն կապված է ներքին սոցիալ-տնտեսական զարգացման հետ:
Keywords: Экономика, управление хозяйством и его отраслями